(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The realm of operations management has undergone a transformative shift in recent years, driven by advancements in machine learning and optimization techniques. This article delves into the intersection of learning and optimal management of operations, exploring how the integration of these two fields has revolutionized industries and propelled organizations toward unprecedented levels of efficiency and productivity. Through the synergy of data-driven insights, predictive analytics, and adaptive strategies, businesses are now empowered to streamline processes, make informed decisions, and achieve operational excellence like never before.